MELANOMA KONJUNGTIVA - Saerang, Josefien M.; Rares, Laya M. (Jurnal Biomedik : JBM, 2011)
Abstract: Conjunctival melanoma is a very rare tumor of the eye which can be fatal. We reported a 42-year-old female having had a black tumor in her right eye for 6 months before she was admitted to the hospital.  This tumor was neither painful, itchy, nor bleeding. The tumor was derived from a nevus. Vision of the right eye was 6/15, corrected with C=100X1050 (6/9) and vision of the left eye was 6/6. The field of vision of the right eye was limited to the lateral part; color vision test was normal; Amsler grid test was normal; pupils were isocor; and Relative Afferent Papillary Defect (RAPD) was negative. Movements of the right eye ball were normal, except for the right temporal part due to the tumor. The anterior segment of the right eye was normal. A funduscopy examination of the right eye showed that the optic papilla, retina, and macula were within normal limits. Routine blood examination, liver function, kidney function, lipid profile, clotting time, and bleeding time were within normal limits. ECG was within normal limits, and a chest X-ray showed no metastase. Based on all examinations, this patient was diagnosed as having conjunctival melanoma, associated with simple hypermetropic astigmatisme, and presbyopia. Key words: melanoma, tumor.     Abstrak: Melanoma konjungtiva merupakan jenis tumor yang sangat jarang dan dapat berakibat fatal. Kami melaporkan seorang wanita berusia 42 tahun, datang ke poliklinik mata dengan keluhan benjolan berwarna hitam di mata kanan sejak 6 bulan sebelum dirawat di rumah sakit. Benjolan tidak nyeri, tidak gatal dan tidak berdarah. Benjolan berasal dari nevus yang tumbuh semakin besar. Visus okuli dekstra (VOD) 6/15 yang dapat dikoreksi dengan kacamata C+100X105º menjadi 6/9 dan visus okuli sinistra (VOS) 6/6. Lapangan pandang okuli dekstra terbatas di lateral kanan, tes color vision dan amsler grid normal, pupil isokor, Relative Afferent Papillary Defect (RAPD) negatif. Gerakan bolamata masih dalam batas normal ke segala arah kecuali ke temporal kanan agak terhalang karena adanya tumor. Segmen anterior okuli sinistra dalam batas normal. Pada funduskopi okuli dekstra dan sinistra: papil nervus optikus, retina dan makula dalam batas normal. Laboratorium darah rutin, fungsi hati, ginjal, profil lipid, clotting time dan bleeding time dalam batas normal. Pemeriksaan EKG dalam batas normal dan X-foto toraks  tidak terdapat metastase. Pasien didiagnosis melanoma konjungtiva yang disertai astigmatisma hipermetropikus simpleks OD dan presbiopia. Kata kunci: melanoma, tumor.